Občutki varnosti pri študentih Univerze v Mariboru - Meško, Gorazd (Teorija in praksa, 2026)
The article focuses on feelings of safety and perceptions of security problems among students of the University of Maribor, particularly at faculties and places of study. A study was conducted in 2025, involving 564 male and female students from all faculties at the University of Maribor. Statistical analyses highlighted correlations between relations on the faculty level and perceptions of safety at the place of study, as well as perceptions of safety at faculties among students. The results also revealed differences in perceptions of security problems at the study site and the consequences of victimisation between male and female students.
Keywords: Kriminal; odnosi; relations; safety; students; študenti; University of Maribor; Univerza v Mariboru; varnost; Varnost (psihologija); victimisation; viktimizacija; Višje in visoke šole